Low-smoke halogen-free composite flame retardant as well as preparation method and application thereof
By using materials such as magnesium hydroxide, potassium formate and wollastonite in low-smoke halogen-free cables to prepare composite flame retardant, the problem of excessive addition of existing flame retardant is solved, and the effect of maintaining good flame retardant effect at low addition amounts and improving elongation at break is achieved.
Patent Information
- Application Number
- CN202510175145.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-25
AI Technical Summary
In existing low-smoke halogen-free cables, the amount of commonly used flame retardant added is too high, resulting in a decrease in the mechanical properties of the cable, especially the poor elongation of break, which limits its large-scale application.
By reacting the ultrafine magnesium hydroxide powder with potassium formate in anhydrous ethanol, a composite was obtained and reacted with wollastonite and silane coupling agent to prepare a low-smoke halogen-free composite flame retardant.
The composite flame retardant can achieve a flame retardant effect comparable to the existing flame retardant at a lower addition amount, and at the same time significantly improve the elongation of the cable break.
Smart Images

Figure CN119875199A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flame retardants, and in particular to a low-smoke halogen-free composite flame retardant and a preparation method and application thereof. Background Art
[0002] Halogen-containing (especially bromine-containing) flame-retardant polymer systems have outstanding flame-retardant effects. For example, polyvinyl chloride (PVC) in the wire and cable industry still plays an important role in insulating materials such as insulating sheaths. However, when PVC burns, it not only releases a large amount of smoke, but also corrosive and toxic gases. Therefore, seeking alternatives to PVC has become a focus of research and development.
[0003] Low smoke halogen-free cable refers to an environmentally friendly cable made of polymers that do not contain halogens (F, Cl, Br, I, At), and do not contain toxic and harmful substances such as lead, cadmium, chromium, and mercury, and does not emit toxic smoke when burned. The low smoke and halogen-free characteristics of the cable can significantly reduce the spread of fire, and the low smoke concentration, high visibility, and small release of harmful gases make it easy to evacuate people when a fire occurs. On the other hand, the gas released by low smoke and halogen-free cables when burning is less corrosive, avoiding damage to instruments and equipment; at the same time, the halogen-free characteristics greatly improve the cable's resistance to aging, UV rays and other radiation, and extend the service life of the cable.
[0004] In low-smoke halogen-free cables, commonly used low-smoke halogen-free flame retardants are aluminum hydroxide and magnesium hydroxide. In order to meet the flame retardant requirements, the flame retardant needs to be added to more than 50%, which is bound to cause a decrease in the mechanical properties of the cable, especially the elongation at break, which seriously restricts the large-scale application of low-smoke halogen-free cables.
[0005] Therefore, there is an urgent need to develop a flame retardant that can significantly reduce the amount of addition while still allowing the cable to have a good flame retardant effect, while improving the mechanical properties of the cable, especially the elongation at break. Summary of the invention
[0006] The purpose of the present invention is to provide a low-smoke halogen-free composite flame retardant and a preparation method and application thereof in view of the deficiencies in the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a low-smoke halogen-free composite flame retardant, comprising the following steps:
[0009] 1) reacting ultrafine magnesium hydroxide powder and potassium formate in anhydrous ethanol to obtain a composite;
[0010] 2) The composite, wollastonite and silane coupling agent are reacted to obtain a low-smoke halogen-free composite flame retardant.
[0011] Preferably, in step 1), the mass ratio of the ultrafine magnesium hydroxide powder to potassium formate is 7-9:1-3.
[0012] Preferably, the reaction temperature in step 1) is 60-80° C., and the reaction time is 10-30 min.
[0013] Preferably, in step 2), the mass ratio of the composite to wollastonite is 8-15:1, and the mass of the silane coupling agent is 0.1-2% of the total mass of the composite and wollastonite.
[0014] Preferably, the reaction temperature in step 2) is 70-90° C., and the reaction time is 20-40 min.
[0015] Preferably, the particle size of the ultrafine magnesium hydroxide powder in step 1) is 0.5 to 3 μm;
[0016] Step 2) The wollastonite is needle-shaped wollastonite, and the particle size of the needle-shaped wollastonite is 1 to 4 μm.
[0017] Preferably, the ultrafine magnesium hydroxide powder in step 1) is prepared by ball milling magnesium hydroxide ore and a grinding aid.
[0018] Preferably, the grinding aid is triethanolamine, and the mass of the grinding aid is 5-9‰ of the mass of the magnesium hydroxide ore;
[0019] The medium used in the ball mill is zirconia beads, the ball-to-material ratio is 2.2-2.5:1, the rotation speed of the ball mill is 3000-4000 r / min, and the ball milling time is 90-150 min.
[0020] The present invention also provides a low-smoke halogen-free composite flame retardant prepared by the preparation method.
[0021] The present invention also provides application of the low-smoke halogen-free composite flame retardant in low-smoke halogen-free cables.
[0022] Beneficial effects of the present invention:
[0023] The low-smoke halogen-free composite flame retardant prepared by the present invention through the interaction between magnesium hydroxide, potassium formate and wollastonite can achieve a flame retardant effect equivalent to that of the existing flame retardant at a lower addition amount, and at the same time improve the elongation at break of the low-smoke halogen-free cable. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a flow chart of the preparation method of the low-smoke halogen-free composite flame retardant. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing a low-smoke halogen-free composite flame retardant, comprising the following steps:
[0026] 1) reacting ultrafine magnesium hydroxide powder and potassium formate in anhydrous ethanol to obtain a composite;
[0027] 2) The composite, wollastonite and silane coupling agent are reacted to obtain a low-smoke halogen-free composite flame retardant.
[0028] In the present invention, the mass ratio of the ultrafine magnesium hydroxide powder and potassium formate in step 1) is preferably 7-9:1-3, more preferably 7.5-8.5:1.5-2.5, and more preferably 8:2.
[0029] In the present invention, the amount of anhydrous ethanol in step 1) is sufficient to completely disperse the ultrafine magnesium hydroxide powder and potassium formate.
[0030] In the present invention, potassium formate can catalyze the breakage and recombination of the alkane molecular chains of the polymer during the combustion process, generate CO2 and H2O, and thus cause self-extinguishing phenomenon, while maintaining a relatively high residual carbon rate and improving the flame retardant effect.
[0031] In the present invention, the reaction temperature in step 1) is preferably 60-80°C, more preferably 65-75°C, and more preferably 70°C; the reaction time is preferably 10-30 min, more preferably 15-25 min, and more preferably 20 min.
[0032] In the present invention, the mass ratio of the composite and wollastonite in step 2) is preferably 8-15:1, more preferably 9-13:1, and more preferably 10-12:1; the mass of the silane coupling agent is preferably 0.1-2% of the total mass of the composite and wollastonite, more preferably 0.5-1.5%, and more preferably 1%.
[0033] In the present invention, wollastonite has high temperature resistance, fire resistance and flame retardancy. During the combustion of the material, wollastonite can form a solid amorphous silicon protective layer, which can effectively isolate the heat generated by the material in the protective layer and the combustible gas from propagating outward, causing the material to self-extinguish and achieve synergistic flame retardancy.
[0034] In the present invention, in step 2), the composite and wollastonite are preferably mixed first, and then a silane coupling agent is added; the silane coupling agent preferably comprises one or more of aminosilane, vinylsilane, epoxysilane and dimethyldichlorosilane.
[0035] In the present invention, the reaction temperature in step 2) is preferably 70-90°C, more preferably 75-85°C, and more preferably 80°C; the reaction time is preferably 20-40 min, more preferably 25-35 min, and more preferably 30 min.
[0036] In the present invention, the particle size of the ultrafine magnesium hydroxide powder in step 1) is preferably 0.5 to 3 μm, more preferably 1 to 2.5 μm, and more preferably 1.5 to 2 μm;
[0037] In step 2), the wollastonite is preferably needle-shaped wollastonite, and the particle size of the needle-shaped wollastonite is preferably 1 to 4 μm, more preferably 2 to 3 μm, and more preferably 2.5 μm.
[0038] In the present invention, the ultrafine magnesium hydroxide powder in step 1) is preferably prepared by ball milling magnesium hydroxide ore and a grinding aid.
[0039] In the present invention, the particle size of the magnesium hydroxide ore is preferably 15 to 25 mm, more preferably 20 mm; the mass content of magnesium hydroxide in the magnesium hydroxide ore is preferably ≥95%, more preferably ≥98%.
[0040] In the present invention, the grinding aid is preferably triethanolamine, and the mass of the grinding aid is preferably 5-9‰ of the mass of the magnesium hydroxide ore, more preferably 6-8‰, and more preferably 7‰;
[0041] The medium used in the ball mill is preferably zirconia beads, and the ball-to-material ratio is preferably 2.2-2.5:1, and more preferably 2.3-2.4:1; the rotation speed of the ball mill is preferably 3000-4000 r / min, and more preferably 3300-3800 r / min, and more preferably 3600 r / min; the ball milling time is preferably 90-150 min, and more preferably 100-140 min, and more preferably 120 min.
[0042] In the present invention, the grinding aid can eliminate the aggregation between powder particles, increase the dispersibility and fluidity between particles, and improve the ball milling efficiency.
[0043] The present invention also provides a low-smoke halogen-free composite flame retardant prepared by the preparation method.
[0044] The present invention also provides application of the low-smoke halogen-free composite flame retardant in low-smoke halogen-free cables.
[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0046] Example 1
[0047] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.2:1, and the ball milling was carried out at a speed of 3600 r / min for 90 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0048] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 7:3, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 70°C for 20 minutes to obtain a composite. Stir the composite and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 2.5μm) in a mass ratio of 15:1 at a speed of 2000r / min for 5 minutes, then add r-aminopropyl triethoxysilane (the mass of r-aminopropyl triethoxysilane is 1% of the total mass of the composite and needle-shaped wollastonite), and react at 80°C for 30 minutes at a speed of 2000r / min to obtain a low-smoke halogen-free composite flame retardant.
[0049] Example 2
[0050] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.5:1, and the ball milling was carried out at a speed of 3600 r / min for 120 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0051] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 8:2, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 70°C for 20 minutes to obtain a composite. Stir the composite and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 2.5μm) in a mass ratio of 15:1 at a speed of 2000r / min for 5 minutes, then add triethoxyvinylsilane (the mass of triethoxyvinylsilane is 1% of the total mass of the composite and needle-shaped wollastonite), and react at 80°C for 30 minutes at a speed of 2000r / min to obtain a low-smoke halogen-free composite flame retardant.
[0052] Example 3
[0053] The magnesium hydroxide ore with a magnesium hydroxide mass content of 98% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 98%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.3:1, and the ball milling was carried out at a speed of 3600 r / min for 120 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0054] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 9:1, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 70°C for 20 minutes to obtain a composite. Stir the composite and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 2.5μm) in a mass ratio of 15:1 at a speed of 2000r / min for 5 minutes, then add silane coupling agent KH-560 (the mass of silane coupling agent KH-560 is 1% of the total mass of the composite and needle-shaped wollastonite), and react at 80°C for 30 minutes at a speed of 2000r / min to obtain a low-smoke halogen-free composite flame retardant.
[0055] Example 4
[0056] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.4:1, and the ball milling was carried out at a speed of 3600 r / min for 120 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0057] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 9:1, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 70°C for 20 minutes to obtain a composite. Stir the composite and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 2.5μm) in a mass ratio of 12:1 at a speed of 2000r / min for 5 minutes, then add dimethyldichlorosilane (the mass of dimethyldichlorosilane is 1% of the total mass of the composite and needle-shaped wollastonite), and react at 80°C for 30 minutes at a speed of 2000r / min to obtain a low-smoke halogen-free composite flame retardant.
[0058] Example 5
[0059] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.2:1, and the ball milling was carried out at a speed of 3600 r / min for 120 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0060] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 9:1, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 70°C for 20 minutes to obtain a composite. Stir the composite and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 2.5μm) in a mass ratio of 10:1 at a speed of 2000r / min for 5 minutes, then add r-aminopropyl triethoxysilane (the mass of r-aminopropyl triethoxysilane is 1% of the total mass of the composite and needle-shaped wollastonite), and react at 80°C for 30 minutes at a speed of 2000r / min to obtain a low-smoke halogen-free composite flame retardant.
[0061] Example 6
[0062] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.2:1, and the ball milling was carried out at a speed of 3600 r / min for 120 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0063] The magnesium hydroxide ultrafine powder and potassium formate with a mass ratio of 9:1 were mixed, and anhydrous ethanol was added to completely disperse the magnesium hydroxide ultrafine powder and potassium formate to obtain a mixture, and the mixture was placed at 70°C for 20 minutes to obtain a composite. The composite with a mass ratio of 8:1 and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 2.5μm) were stirred at a speed of 2000r / min for 5 minutes, and then r-aminopropyl triethoxysilane (the mass of r-aminopropyl triethoxysilane is 1% of the total mass of the composite and needle-shaped wollastonite) was added, and the mixture was reacted at 80°C for 30 minutes at a speed of 2000r / min to obtain a low-smoke halogen-free composite flame retardant.
[0064] Example 7
[0065] The magnesium hydroxide ore with a magnesium hydroxide mass content of 98% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 15mm and a magnesium hydroxide mass content of 98%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 5‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2mm (including 1mm and excluding 2mm), zirconium oxide beads with a particle size of 2 to 4mm (including 2mm and excluding 4mm) and zirconium oxide beads with a particle size of 4 to 8mm (including 4mm and including 8mm) was 1:4:2, the ball-to-material ratio was set to 2.2:1, and the ball milling was performed at a speed of 4000 / min for 100min. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 0.5μm.
[0066] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 7.5:2.5, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 60°C for 30 minutes to obtain a composite. Stir the composite and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 1 μm) in a mass ratio of 13:1 at a speed of 2000 r / min for 5 minutes, then add r-aminopropyl triethoxysilane (the mass of r-aminopropyl triethoxysilane is 0.1% of the total mass of the composite and needle-shaped wollastonite), and react at 90°C for 20 minutes at a speed of 2000 r / min to obtain a low-smoke halogen-free composite flame retardant.
[0067] Example 8
[0068] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 25mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 9‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2mm (including 1mm and excluding 2mm), zirconium oxide beads with a particle size of 2 to 4mm (including 2mm and excluding 4mm) and zirconium oxide beads with a particle size of 4 to 8mm (including 4mm and including 8mm) was 1:4:2, the ball-to-material ratio was set to 2.2:1, and the ball milling was carried out at a speed of 3000r / min for 150min. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 3μm.
[0069] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 8.5:1.5, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 80°C for 10 minutes to obtain a composite. Stir the composite and needle-shaped wollastonite (the particle size of the needle-shaped wollastonite is 4μm) in a mass ratio of 9:1 at a speed of 2000r / min for 5 minutes, then add r-aminopropyl triethoxysilane (the mass of r-aminopropyl triethoxysilane is 2% of the total mass of the composite and needle-shaped wollastonite), and react at 70°C for 40 minutes at a speed of 2000r / min to obtain a low-smoke halogen-free composite flame retardant.
[0070] Comparative Example 1
[0071] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.2:1, and the ball milling was carried out at a speed of 3600 r / min for 120 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0072] The magnesium hydroxide ultrafine powder and r-aminopropyltriethoxysilane (the mass of r-aminopropyltriethoxysilane is 1% of the mass of the magnesium hydroxide ultrafine powder) are mixed at a rotation speed of 2000 r / min, and reacted at 80° C. for 30 minutes to obtain a flame retardant.
[0073] Comparative Example 2
[0074] The magnesium hydroxide ore with a magnesium hydroxide mass content of 95% was crushed and cleaned to obtain a magnesium hydroxide ore with a particle size of 20 mm and a magnesium hydroxide mass content of 95%. The magnesium hydroxide ore and triethanolamine (the mass of triethanolamine is 7‰ of the mass of the magnesium hydroxide ore) were added to the ball mill, and zirconium oxide beads were used as ball milling media. The composition of the ball milling media was: the mass ratio of zirconium oxide beads with a particle size of 1 to 2 mm (including 1 mm and excluding 2 mm), zirconium oxide beads with a particle size of 2 to 4 mm (including 2 mm and excluding 4 mm) and zirconium oxide beads with a particle size of 4 to 8 mm (including 4 mm and including 8 mm) was 1:4:2, the ball-to-material ratio was set to 2.2:1, and the ball milling was carried out at a speed of 3600 r / min for 120 minutes. After the ball milling, the ball milling product was air-selected and classified by a classifier to obtain a magnesium hydroxide ultrafine powder with a particle size of 1.5 μm.
[0075] Mix ultrafine magnesium hydroxide powder and potassium formate in a mass ratio of 9:1, add anhydrous ethanol to completely disperse the ultrafine magnesium hydroxide powder and potassium formate to obtain a mixture, and place the mixture at 70°C for 20 minutes to obtain a composite. Mix the composite and r-aminopropyltriethoxysilane (the mass of r-aminopropyltriethoxysilane is 1% of the mass of the composite) at a speed of 2000 r / min, place at 80°C for 30 minutes to obtain a flame retardant.
[0076] Application Example 1
[0077] 60g of the composite flame retardant of Example 1, 20g of EVA, 5g of maleic anhydride grafted PP compatibilizer (the grafting rate of maleic anhydride in the maleic anhydride grafted PP compatibilizer is 0.7-0.9%), 10g of polyethylene, and 1g of silicone masterbatch were placed in a double-roll mill and milled at 155°C for 15min. Then, a composite sample with a thickness of 4mm was pressed into a flat vulcanizer at 10MPa and 155°C.
[0078] Application Example 2
[0079] The composite flame retardant in Application Example 1 is replaced by the composite flame retardant in Example 2, and the rest is the same as Application Example 1.
[0080] Application Example 3
[0081] The composite flame retardant in Application Example 1 is replaced by the composite flame retardant in Example 3, and the rest is the same as Application Example 1.
[0082] Application Example 4
[0083] The composite flame retardant in Application Example 1 is replaced by the composite flame retardant in Example 4, and the rest is the same as Application Example 1.
[0084] Application Example 5
[0085] The composite flame retardant in Application Example 1 is replaced by the composite flame retardant in Example 5, and the rest is the same as Application Example 1.
[0086] Application Example 6
[0087] The mass of the composite flame retardant in Application Example 5 is modified to 55 g, and the rest is the same as Application Example 5.
[0088] Application Example 7
[0089] The mass of the composite flame retardant in Application Example 5 is modified to 50 g, and the rest is the same as Application Example 5.
[0090] Application Example 8
[0091] The mass of the composite flame retardant in Application Example 5 is modified to 45 g, and the rest is the same as Application Example 5.
[0092] Application Example 9
[0093] The composite flame retardant in Application Example 1 is replaced by the composite flame retardant in Example 6, and the rest is the same as Application Example 1.
[0094] Application Comparative Example 1
[0095] The composite flame retardant in Application Example 5 is replaced by the flame retardant in Comparative Example 1, and the rest is the same as in Application Example 1.
[0096] Application Comparative Example 2
[0097] The composite flame retardant in Application Example 5 is replaced by the flame retardant in Comparative Example 2, and the rest is the same as in Application Example 1.
[0098] The composite sample was cut into test specimens by a pneumatic cutting machine for performance testing. The test results are shown in Table 1.
[0099] The tensile strength and elongation at break are tested according to GB / T 1040.1-2018, and the limiting oxygen index is tested according to GB / T2406.2-2009.
[0100] Table 1 Performance test results of composite samples
[0101]
[0102]
[0103] It can be seen from Table 1 that the effect of the flame retardant of a single flame retardant component (magnesium hydroxide) is significantly lower than that of the composite flame retardant of magnesium hydroxide, potassium formate, and wollastonite, and the effect of the composite flame retardant of magnesium hydroxide and potassium formate is also lower than that of the composite flame retardant of magnesium hydroxide, potassium formate, and wollastonite. This result shows that in the composite flame retardant of the present invention, magnesium hydroxide, potassium formate, and wollastonite have a synergistic flame retardant effect, and the composite flame retardant of the present invention can achieve a flame retardant effect comparable to that of the existing flame retardant at a lower content, and can significantly improve the elongation at break of the cable.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a low-smoke halogen-free composite flame retardant, characterized in that: The following steps are included: 1) reacting ultrafine magnesium hydroxide powder and potassium formate in anhydrous ethanol to obtain a composite; 2) The composite, wollastonite and silane coupling agent are reacted to obtain a low-smoke halogen-free composite flame retardant.
2. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of the ultrafine magnesium hydroxide powder to potassium formate is 7-9:1-3.
3. The preparation method according to claim 1 or 2, characterized in that: Step 1) The reaction temperature is 60-80°C and the reaction time is 10-30 minutes.
4. The preparation method according to claim 3, characterized in that: Step 2) The mass ratio of the composite to wollastonite is 8-15:1, and the mass of the silane coupling agent is 0.1-2% of the total mass of the composite and wollastonite.
5. The preparation method according to claim 4, characterized in that: Step 2) The reaction temperature is 70-90°C and the reaction time is 20-40 minutes.
6. The preparation method according to claim 4 or 5, characterized in that: Step 1) The particle size of the magnesium hydroxide ultrafine powder is 0.5 to 3 μm; Step 2) The wollastonite is needle-shaped wollastonite, and the particle size of the needle-shaped wollastonite is 1 to 4 μm.
7. The preparation method according to claim 6, characterized in that: Step 1) The ultrafine magnesium hydroxide powder is prepared by ball milling magnesium hydroxide ore and a grinding aid.
8. The preparation method according to claim 7, characterized in that: The grinding aid is triethanolamine, and the mass of the grinding aid is 5-9‰ of the mass of the magnesium hydroxide ore; The medium used in the ball mill is zirconia beads, the ball-to-material ratio is 2.2-2.5:1, the rotation speed of the ball mill is 3000-4000 r / min, and the ball milling time is 90-150 min.
9. The low-smoke halogen-free composite flame retardant prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the low-smoke zero-halogen composite flame retardant according to claim 9 in low-smoke zero-halogen cables.